The Tale of the Tribe : Ezra Pound and the Modern Verse Epic. - Bernstein, Michael André (Princeton University Press, 2014)
Michael Andre Bernstein offers a systematic analysis of the tradition of modern epic poetry--its different structural problems and their diverse but inter-related solutions, and considers issues central to contemporary literary and philosophical theory. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in du.
Keywords: Pound, Ezra, -- 1885-1972. -- Cantos.; Williams, William Carlos, -- 1883-1963. -- Paterson.; Olson, Charles, -- 1910-1970. -- Maximus poems.; Cantos (Pound, Ezra); Maximus poems (Olson, Charles); American poetry -- 20th century -- History and criticism.; Epic poetry, American -- History and criticism.; Poésie américaine -- 20e siècle -- Histoire et critique.; Poésie épique américaine -- Histoire et critique.; LITERARY CRITICISM -- Poetry.; American poetry; Epic poetry, American; 1900-1999; Criticism, interpretation, etc.